2017
DOI: 10.1186/s12876-017-0611-z
|View full text |Cite
|
Sign up to set email alerts
|

Proteinuria and baseline renal function predict mortality and renal outcomes after sirolimus therapy in liver transplantation recipients

Abstract: BackgroundChronic kidney disease is a significant complication after liver transplantation (LT), but the role of pre-existing renal insufficiency and proteinuria remains unclear among LT recipients receiving sirolimus.MethodsWe assessed the effects of proteinuria and baseline renal function on long-term renal and survival outcomes among 576 LT recipients who received SRL in a medical center between 2005 and 2014. Renal outcomes were the incidences of >50% reduction in their baseline estimated glomerular filtra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Patients with a higher risk of renal function deterioration, such as preexisting CKD, higher Model for End-Stage Liver Disease score, renal function, and proteinuria, should be carefully monitored after mTORI conversion to reevaluate the necessity of mTORI. 4 Although everolimus has higher oral bioavailability and better metabolic stability than sirolimus, the difference on renoprotection was insignificant in our study cohort. Glover et al conducted a systemic review and meta-analysis of randomized control trials in liver transplant recipients with mTORI conversion, in which both arms showed favorable trends towards everolimus or sirolimus (mean differences of eGFR in everolimus vs sirolimus = +0.44,95% CI [0.16,0.71] vs +0.37, 95% CI -0.04-0.77).…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Patients with a higher risk of renal function deterioration, such as preexisting CKD, higher Model for End-Stage Liver Disease score, renal function, and proteinuria, should be carefully monitored after mTORI conversion to reevaluate the necessity of mTORI. 4 Although everolimus has higher oral bioavailability and better metabolic stability than sirolimus, the difference on renoprotection was insignificant in our study cohort. Glover et al conducted a systemic review and meta-analysis of randomized control trials in liver transplant recipients with mTORI conversion, in which both arms showed favorable trends towards everolimus or sirolimus (mean differences of eGFR in everolimus vs sirolimus = +0.44,95% CI [0.16,0.71] vs +0.37, 95% CI -0.04-0.77).…”
Section: Discussionmentioning
confidence: 53%
“…Notably, mTORIs present adverse effects such as oral ulcer, dyslipidemia, impairment of wound healing, and proteinuria. 4,5,11 The adverse events observed in our patients, who failed to remain on a same mTORI for at least 6 months, were oral ulceration, dyslipidemia, and unsatisfactory trough concentrations in up to 11.4% and 13.3% in sirolimus and everolimus users, respectively. Our findings and previous evidence suggested that when assessing the appropriateness of mTORI conversion therapy, the benefits and risks should be balanced individually.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Post-transplant diabetes mellitus represents a major adverse effect of immunosuppressive drugs 1 4 and is associated with high cumulative incidence of cardiac events, vascular disease, and overall impaired survival rates 5 . Sirolimus (rapamycin) was introduced in the Edmonton immunosuppression protocol in islet transplant recipients 6 , 7 , attempting to minimize the diabetogenic effects observed with corticosteroids and other immunosuppressive regimens.…”
Section: Introductionmentioning
confidence: 99%